Dual-functional hierarchical mechanical metamaterial for vibration insulation and energy absorption. (15th November 2022) - Zhang, Linwei; Bai, Zhonghao; Chen, Yafeng
Highlights: Dual-functional hierarchical mechanical metamaterials are proposed for simultaneous vibration insulation and energy absorption. The effects of the hierarchical configurations on the band gap distributions and energy absorption efficiency are systematically studied. The parameter analysis is performed to analyze the effects of structural parameters on the band gap characteristics and crushing performance. The multi-objective optimization is employed to seek the optimal structural design. Abstract: In this study, the vibration isolation characteristics and crushing behaviors of novel hierarchical mechanical metamaterials are investigated. Numerical analyses are carried out for a class of mechanical metamaterials with different hierarchical configurations. The effects of the hierarchical configurations on the band gap distributions and energy absorption efficiency are carefully studied. The results indicate that the hierarchical configuration has remarkable potential in broadening the band gap and improving energy-absorbing efficiency. Moreover, the configuration (S3) with the best performance of vibration isolation and energy absorption among the proposed metamaterials is determined. The parameter analysis on S3 is further performed to analyze the effects of structural parameters on the band gap characteristics and crushing performance. Finally, multi-objective optimization is employed to seek optimal structural parameters of S3 for enhancing the gap-midgap ratio and the specific energy absorption, simultaneously. This study provides effective guidance for designing mechanical metamaterials with excellent vibration isolation capacity and energy absorption efficiency.